The Changing Wealth of Nations : Measuring Sustainable Development in the New Millennium - The World Bank (Washington, D.C. World Bank, 2011)
This book is about development and measuring development progress. While precise definitions may vary, development is, at heart, a process of building wealth, the produced, natural, human, and institutional capital which is the source of income and wellbeing. Divided into 2 major parts, coverage includes a big picture of changes in wealth by income group and geographic region as well as case studies in wealth accounting and how it is being implemented in various countries
Include Index
Keywords: Sustainable development -- Economic indicators